Cognitive style: Student problem solving on integer count operations - Jemamut, Natalia; Rochaminah, Sutji; Ismaimuza, Dasa; Paloloang, Muhammad Fachri B (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to describe the profile of students who have Field Independent (FI) and Field Dependent (FD) cognitive styles in solving integer counting operation problems. This type of research is descriptive research. The approach used in this study is a qualitative approach. The results of this study show the profile of student problem solving with FI and FD cognitive styles in solving integer counting operation problems. (1) Student problem-solving profile with FI cognitive style in solving integer counting operation problems. Subject FI can determine and declare the elements that are known, that are questioned, and the sufficiency of other elements. Subject FI shows good ability in implementing problem-solving strategies with correct and thorough steps. Subject FI can explain the results of the completion orally and in writing. (2) Student problem-solving profile with FD cognitive style in solving integer counting operation problems. Subject FD can determine and state the elements that are known, that are asked, and the sufficiency of other elements, even though Subject FD reads the question repeatedly and takes a little longer, but Subject FD seems to understand the problem because it can determine and express the information from the question. Subject FD can compile a mathematical model from the problem. However, the mathematical model that was written did not use parentheses, so the sequence of operations did not correspond to the context of the story. Subject FD is still wrong in solving the problem so that the answers obtained are not correct. Subject FD can explain the results of the settlement orally, but does not write them in writing on the answer sheet.